Development of The Software as Services (SaaS) Business Model in The Satusehat Integrated Electronic Medical Record System - Panji Novantara; Ragel Trisudarmo; Fauziah (bit-Tech, 2025)
Digital transformation in the healthcare sector represents a key strategy to enhance operational efficiency and improve the quality of medical services. This study presents the development of a Software as a Service (SaaS)-based Electronic Medical Record (EMR) information system, integrated with SatuSehat, a national health data platform managed by the Ministry of Health of the Republic of Indonesia. The system is designed to improve the accuracy of clinical data recording and expedite access to patient information for healthcare professionals. The development process adopted the Agile methodology, characterized by iterative and incremental stages including requirements analysis, system design, implementation, testing, and evaluation. Agile was selected for its ability to accommodate dynamic user needs and regulatory requirements through continuous feedback loops and adaptive planning. Compliance with national health regulations and data security standards, including Minister of Health Regulation No. 24 of 2022 concerning EMR implementation, guided the entire process. Evaluation of the system demonstrates enhanced efficiency in medical administrative workflows, improved accuracy of patient records, and accelerated clinical decision-making processes. The integration with SatuSehat enables interoperability at a national level, thereby supporting real-time health data exchange and long-term health monitoring systems. From a societal standpoint, the system improves data accessibility for healthcare personnel and elevates the overall quality of care delivered to patients. Economically, the SaaS-based approach reduces operational costs, promotes efficient budgeting, and contributes to the broader digital transformation of healthcare services, particularly in strengthening primary care infrastructure.